Nasal tip support: A finite element analysis of the role of the caudal septum during tip depression. (19th September 2013) - Manuel, Cyrus T.; Leary, Ryan; Protsenko, Dmitriy E.; Wong, Brian J. F.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Although minor and major tip support mechanisms have been described in detail, no quantitative models exist to provide support for the relative contributions of the structural properties of the major alar cartilage, the fibrous attachments to surrounding structures, and the rigid support structures in an objective manner. Study Design The finite element method was used to compute the stress distribution in the nose during simple tip compression, and then identify the specific anatomic structures that resist deformation and thus contribute to tip support. Additionally, the impact of caudal septal resection on nasal tip support was examined. Methods The computer models consisted of three tissue components with anatomically correct geometries for skin and bone derived from computed tomographic data. Septum, upper lateral cartilages, and major alar cartilages were fitted within the model using three‐dimensional computer‐aided design software. Five‐millimeter nasal tip compression was performed on the models with caudal septal resection (3 and 5 mm) and without resection to simulate palpation, then the resulting spatial distribution of stress and displacement was calculated. Results The von Mises stress in the normal model was primarily concentrated along the medial crural angle. As caudal septum length was reduced, stress was redistributed to adjacent soft tissue and bone, resulting in less force acting on the septum. In all models, displacement was greatest near the intermediate crura. Conclusions These models are the first step in the comprehensive mechanical analysis of nasal tip dynamics. Our model supports the concept of the caudal septum and major alar cartilage providing the majority of critical load‐bearing support. Level of Evidence N/A Laryngoscope, 124:649–654, 2014